PERAN KALSIUM MITOCHONDRIAL DAN STRES OKSIDATIF TERHADAP APOPTOSIS PADA PENYAKIT NEURODEGENERATIF - Jan S. Purba* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION IT HAS LONG BEEN KNOWN THAT CALCIUM CA2 SIGNALS GOVERN A HOST OF VITAL CELL FUNCTIONS AND SO ARE NECESSARY FOR CELL SURVIVAL HOWEVER MORE RECENTLY IT HAS BECOME CLEAR THAT CELLULAR CA2 OVERLOAD OR PERTURBATION OF INTRACELLULAR CA2 COMPARTMENTALIZATION CAN CAUSE CYTOTOXICITY AND TRIGGER EITHER APOPTOTIC OR NECROTIC CELL DEATH NEURONAL DEATH UNDERLIES THE SYMPTOMS OF MANY HUMAN NEUROLOGICAL DISORDERS INCLUDING MULTIPLE SCLEROSIS MS ALZHEIMERS DISEASE AD PARKINSONS DISEASE PD AND HUNTINGTONS DISEASES HD STROKE AND AMYOTROPHIC LATERAL SCLEROSIS ALS THE IDENTIFICATION OF SPECIFIC GENETIC AND ENVIRONMENTAL FACTORS RESPONSIBLE FOR THESE DISEASES HAS BOLSTERED EVIDENCE FOR A SHARED PATHWAY OF NEURONAL DEATH INVOLVING OXIDATIVE STRESS PERTURBED CALCIUM HOMEOSTASIS MITOCHONDRIAL DYSFUNCTION AND ACTIVATION OF CYSTEINE PROTEASES CALLED CASPASES WITH THE IDENTIFICATION OF MECHANISMS THAT EITHER PROMOTE OR PREVENT NEURONAL APOPTOSIS COME NEW APPROACHES FOR PREVENTING AND TREATING NEURODEGENERATIVE DISORDERS